Palladium‐Catalysed C−C Bond Forming 4‐Cyanophenyl‐nicotinamide Conjugates; Anti‐Pancreatic Cancer Screening on Capan‐1 Cell Line. Issue 11 (22nd March 2023) - Rahman, Abdul; Belur Ningegowda, Nippu; Kammathalli Siddappa, Manjunatha; Kumar Jain, Sandeep; Malleshappa Kumaraswamy, Honnenahally; Achur, Rajeshwara; Devappa Satyanarayan, Nayak; Malavalli Mahadevan, Kittappa
Abstract: Pancreatic cancer is the most severe, as a consequence of asymptomatic nature and ineffective therapies among all malignancies. Nicotinamides are effective ring systems in the treatment of pancreatic cancer with their wide range of applications. In the present investigation, nicotinamide and 4‐cyanophenyl ring systems are brought together to obtain greater potency. For the process of investigation, PARP1 protein is targeted and evaluated by docking at the active site to determine the protein‐ligand interaction, revealed the potential with the binding affinity of −9.0 to −11.0 Kcal/mol to inhibit the poly ADP‐ribose polymerase 1 (PARP1) pathway. The MTT‐assay assessment of a synthesized series has been performed against Capan‐1 pancreatic cancer cell line. The nicotinamide compounds demonstrated a significant inhibitory effect over Capan‐1 cell line, and 6‐(4‐cyanophenyl)‐N‐(3‐phenylpropyl)nicotinamide exhibited as a potential lead for the development of novel chemotherapeutics against pancreatic cancer. Abstract : The compound 9 d exhibited a greater antiproliferative activity (28.00 μM). Wherein, 9 a with the heteroaryl isoxazole ring system, exhibited reduced antiproliferative activity with an IC50 value of 97.97 μM. Comparatively, the inhibitory activity of 9 d is increased by 3.4 folds.